Intravascular ultrasounds in Portugal: usage trend and outcomes. (26th April 2021) - Marques Pires, C; Galvao Braga, C; Costa, M; Silva, PC; Ferreira, R; Teles, R; Seixo, F; Marques, J; Costa, J; Pereira, H; Cardoso, PP; Silveira, JB; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. INTRODUCTION: The current guidelines on myocardial revascularization recommend the use of Intravascular ultrasounds (IVUS) in selected patients (pts) to optimize stent apposition (IIaB) and to assess severity and optimize treatment of unprotected left main (LM) lesions (IIaB). AIMS: To evaluate the use of IVUS in the last 7 years in Portugal and to assess if the use of IVUS in LM percutaneous coronary intervention (PCI) had impact on outcomes. METHODS: A multicentric retrospective study in which we evaluated the use of IVUS in the last 7 years (2012-2018) in 5 different regions of Portugal in pts submitted to LM and non-LM PCI. A multivariate analysis was performed to assess if the use of IVUS in LM PCI had impact on in-hospital and 1-year follow-up (FUP) MACE (death/ myocardial infarction/need of revascularization). RESULTS: The present study showed a progressive increased use of IVUS in PCI in Portugal (pvalue <0, 001), but with some regional asymmetries: in the Region 1 (pvalue < 0, 001), Region 2 (pvalue = 0, 03) and Region 5 (pvalue = 0, 03) this trend to increased use was observed, but not on Region 3 (pvalue = 0, 15) and Region 4(pvalue = 0, 72). An overall growth in the use of IVUS in LM PCI was also documented (p < 0, 001), but again regional differences were encountered, with Region 2 (pvalue = 0, 37) and Region 3 (pvalue-0, 15) showing no statistically significant progression on its use in this setting. In addition, there was also an increased use of IVUS in non-LM PCI in Portugal (pvalue-0, 02), but on regional analysis only Region 1 showed a significant variation (pvalue-0, 002). Subsequently, we found that inhospital MACE incidence was statistically lower in pts submitted to LM PCI with IVUS guidance (1, 4 vs 3, 9%, p-0, 024), but this wasn't confirmed on multivariate analysis adjusted to confounding factors (pvalue = 0, 309). At 1-year FUP of pts submitted to LM PCI, we found a trend to fewer events with IVUS guidance, but the Kaplan Meier curves (pvalue = 0, 07) and Cox regression analysis (pvalue = 0, 879) didn't demonstrate a significant impact of IVUS on 1-year MACE. CONCLUSION: This study shows that in line with current guidelines the overall use of IVUS in Portugal has been significantly increasing in the last years. Despite a trend to fewer events with IVUS guidance in LM PCI, there wasn't a statistical impact on inhospital and 1-year MACE.